Percutaneous mitral valve repair in recurrent severe mitral valve regurgitation after mitral annuloplasty: MitraClip-in-the-ring as a complementary strategy - Pleger, Sven Torsten; Geis, Nicolas; Kreußer, Michael; Abu Sharar, Haitham; Sebening, Christian; Szabó, Gábor; Katus, Hugo; Raake, Philip (Herz, 2021)
Patients with reduced left ventricular (LV) function undergoing coronary artery bypass graft surgery or/and aortic valve replacement occasionally show severe mitral valve (MV) regurgitation and thus also undergo surgical mitral annuloplasty. Over time, further deterioration of LV function and additional ischemic events cause recurrence of severe MV regurgitation due to the Carpentier IIIb morphology of the MV that is not adequately addressed by the previously implanted annuloplasty ring.
Deutscher Titel auf der Frontdoor: Perkutane Mitralklappenrekonstruktion bei schwerer Mitralinsuffizienz nach Mitralklappenannuloplastie$dMitraClip-in-the-ring als ergänzende Strategie
Published online: 26 November 2019
Gesehen am 20.07.2021